2020
DOI: 10.3390/molecules25133086
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Saponins in Underground Parts of Panax vietnamensis at Different Ages Analyzed by HPLC-UV/ELSD

Abstract: Panax vietnamensis (PV), a wild Panax species discovered in Vietnam in 1973, has been increasingly overexploited due to its economic value and therapeutic uses. This resulted in the development of PV cultivation to meet the market demand. There is little information on the accumulation of saponins in PV during cultivation, but this information could serve as an indication of the appropriate harvest time. In this study we developed an HPLC-UV/ELSD method to simultaneously determine the content of 10 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Saponins do not contain conjugated double bonds that can form chromophores, and are therefore difficult to detect under UV [ 43 , 44 , 45 , 46 , 47 ]. The use of a developer such as sulfuric anisaldehyde [ 48 ], allowed the saponins to take on blue, yellow, green, or purple colors [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Saponins do not contain conjugated double bonds that can form chromophores, and are therefore difficult to detect under UV [ 43 , 44 , 45 , 46 , 47 ]. The use of a developer such as sulfuric anisaldehyde [ 48 ], allowed the saponins to take on blue, yellow, green, or purple colors [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, previous research on VG cultivated in Tra Linh indicated the reverse pattern in the accumulation rate of mass, with the accumulation rate of the main root being four times higher than that of the rhizome [ 21 ]. This result illustrates that the differences in cultivation area might affect the accumulation rate of mass in VG.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, at five years old, the content of M-R1 in the main root and rhizome of VG cultivated in Lam Dong was 3.88% and 4.22%, respectively, which is 25–35 times higher than those of the main root and rhizome of VG growth on Tra Linh Mountain. In addition, the content of V-R2 in the root and rhizome of VG in Lam Dong is 27 times and 25 times higher than the content of V-R2 in the root and rhizome of VG in Tra Linh, respectively [ 21 ]. This significant difference suggests that M-R1 and V-R2 could serve as a potential marker for distinguishing between VG cultivated in Lam Dong and Tra Linh.…”
Section: Resultsmentioning
confidence: 99%
“…Sâm Ngọc Linh (Panax vietnamensis) là loài thực vật đặc hữu ở Việt Nam, phân bố hẹp từ độ cao 1.500 m trở lên tại tỉnh Kon Tum và Quảng Nam. Sâm Ngọc Linh có rất nhiều hợp chất quý hiếm, bao gồm nhóm saponin và non-saponin, được chứng minh có giá trị dược liệu rất cao [1]. Tuy nhiên, tình trạng khai thác quá mức các cá thể tự nhiên đã khiến sâm Ngọc Linh được đưa vào danh mục đỏ của Việt Nam [2], [3].…”
Section: Giới Thiệuunclassified